Sequence-dependent association of alginate with sodium and calcium counterions. (10th February 2017) - Hecht, Hadas; Srebnik, Simcha
Highlights: Molecular simulation of natural sequences of alginate. Dependence of alginate structure on guluronic acid content. Condensation of Na + and Ca 2+ on alginate. Fitting of scattering curves of Ca 2+ -alginate to SAXS models. Abstract: Molecular dynamics simulation is used to study in detail the binding of sodium and calcium ions to alginate chains, and its dependence on the content of guluronic (G) acid residues. Our previous studies showed that chains with different G content associate through different structural mechanisms due to differing degrees of rigidity of the ion-alginate chain complexes. Polymannuronate and polyguluronate chains form highly ordered structures due to their more rigid nature. Heteropolymer chains are more flexible and hence associate at higher ion and alginate concentrations, however, with association behavior that has a clear dependence on G content. The nature of interactions of sodium and calcium ions are shown to differ for poly-M, poly-G, and the heteropolymer compositions. Scattering curves of Ca 2+ -alginate solutions where found to have good agreement with the broken-rod SAXS model with nontrivial but clear dependence on G content, which is explained by chain flexibility and its relation to ion condensation.